ANALISIS JUMLAH PENUMPANG KAPAL PENYEBERANGAN ULEE LHEUE TERHADAP PENERIMAAN RETRIBUSI PELAYANAN PELABUHAN KOTA BANDA ACEH - Muhammad Daud; Yushita Marina (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2017)
Ulee Lheue Port is one of the ferry ports located in the city of Banda Aceh as a transportation to Sabang Weh Island. The city of Sabang is famous as one of the destinations of sharia tourism in Indonesia, therefore the revenue of the region can be obtained from the sea port service levy. As a source of revenue, the acceptance of port service levies is affected by the number of passengers on the ferry. This study aims to analyze whether there is an influence between the number of passenger ships crossing the acceptance of levy services sea port city of Banda Aceh. This research uses quantitative approach and data analysis used is simple regression analysis. The source of this research is taken from the Banda Aceh Statistics Data Report 2012 to 2015. The results show that there is influence between the number of passenger ship crossing to the receipt of levy service of seaport city of Banda Aceh.